Vortex dynamics, statistical mechanics, and planetary atmospheres - Lim, Chjan C., 1959- (World Scientific, 2009)
Vortex Dynamics, Statistical Mechanics, and Planetary Atmospheres introduces the reader with a background in either fluid mechanics or statistical mechanics to the modeling of planetary atmospheres by barotropic and shallow-water models. These potent models are introduced in both analytical and numerical treatments highlighting the ways both approaches inform and enlighten the other. This book builds on Vorticity, Statistical Mechanics, and Monte Carlo Simulations by Lim and Nebus in providing a rare introduction to this intersection of research fields. While the book reaches the cutting edge of atmospheric models, the exposition requires little more than an undergraduate familiarity with the relevant fields of study, and so this book is well suited to individuals hoping to swiftly learn an exciting new field of study. With inspiration drawn from the atmospheres of Venus and of Jupiter, the physical relevance of the work is never far from consideration, and the bounty of results shows a new and fruitful perspective with which to study planetary atmospheres.